ASK - ANSWER - COMMENT - VOTE - CREATE

Join the MathsGee Club | Ask your Question | StartUps

Let the left hand side be: x = 0.3333333…… (i)

Multiplying (i) by 10 gives: 10x = (10)(0.3333333……) = 3.333333...... (ii)

(ii) - (i) gives: 10x - x = 3.333333...... - 0.3333333……

9x = 3

x = 3/9 = (1/3)

Therefore the initial statement is true

Login using Facebook Login using LinkedIn Login using Twitter

Join the MathsGee Answer Hub community and get study support for success - MathsGee Answer Hub provides answers to subject-specific educational questions for improved outcomes.

On MathsGee Answers, you can:

Posting on MathsGee